Gadoxetic acid-enhanced hepatobiliary-phase magnetic resonance imaging for delineation of focal nodular hyperplasia: superiority of high-flip-angle imaging - Sheng, Ruofan; Palm, Viktoria; Mayer, Philipp; Mokry, Theresa; Berger, Anne Katrin; Weiss, Karl Heinz; Longerich, Thomas; Kauczor, Hans-Ulrich; Weber, Tim (Journal of computer assisted tomography, 2018)
ObjectiveThe aim of this study was to investigate whether hepatobiliary-phase (HBP) flip-angle (FA) increase to 25° improves conspicuity of focal nodular hyperplasia (FNH) and enables HBP delay reduction.MethodsThis was a retrospective study of 23 patients with 46 FNHs. In each patient, HBP was perf